Diverse flowering responses subjecting to ambient high temperature in soybean under short‐day conditions. Issue 4 (12th January 2023) - Tang, Yang; Lu, Sijia; Fang, Chao; Liu, Huan; Dong, Lidong; Li, Haiyang; Su, Tong; Li, Shichen; Wang, Lingshuang; Cheng, Qun; Liu, Baohui; Lin, Xiaoya; et al.
Summary: Flowering time is one of important agronomic traits determining the crop yield and affected by high temperature. When facing high ambient temperature, plants often initiate early flowering as an adaptive strategy to escape the stress and ensure successful reproduction. However, here we find opposing ways in the short‐day crop soybean to respond to different levels of high temperatures, in which flowering accelerates when temperature changes from 25 to 30 °C, but delays when temperature reaches 35 °C under short day. phyA‐E1, possibly photoperiodic pathway, is crucial for 35 °C‐mediated late flowering, however, does not contribute to promoting flowering at 30 °C. 30 °C‐induced up‐regulation of FT2a and FT5a leads to early flowering, independent of E1. Therefore, distinct responsive mechanisms are adopted by soybean when facing different levels of high temperatures for successful flowering and reproduction.